Step-by-step explanation:
15/25 - 1 = -0.4 = -40%
The price was decreased by 40%.
Answer:
see attachment
Step-by-step explanation:
y = x^2 + 4x + 7
y = x^2 + 4x + 1
y = x^2 + 4x - 3
Answer:
y=x^2+4x+7
Step-by-step explanation:
y=(x+2)(x+2)-3
y=x^2+2x+2x+4-3
y=x^2+4x+7
Answer:
C. y = x² + 4x + 1
Step-by-step explanation:
y = (x + 2)² - 3
y = x² + 4x + 4 - 3
y = x² + 4x + 1
40.00 - 19.50 = 20.50
20.50 ÷ by 2 = 10.25
each video cost
Geno now wants to write an equation to solve the problem. He let g = cost of a video game.
Which equation can be used to find the cost of each video game?
A. 2g = 19.5
B. 2g + 40 = 19.5
C. 2g –19.5 = 40
D. 19.5 + 2g = 40
Answer:
B 9.8
Step-by-step explanation:
Answer:
A. and
Step-by-step explanation:
We have been given a system of equations. We are asked to find the solution of our given system.
Equate both equations:
Split the middle term:
Use zero product property:
Now, we will substitute both values of x, in our given equation to solve for y.
One solution:
2nd solution:
Therefore, option A is the correct choice.
Answer:
A
Step-by-step explanation:
Given the 2 equations
y = x² - 4x + 8 → (1)
y = 2x + 3 → (2)
Since both express y in terms of x we can equate the left sides, that is
x² - 4x + 8 = 2x + 3 ( subtract 2x + 3 from both sides )
x² - 6x + 5 = 0 ← in standard form
(x - 1)(x - 5) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 5 = 0 ⇒ x = 5
Substitute these values into (2) for corresponding values of y
x = 1 : y = (2 × 1) + 3 = 2 + 3 = 5 ⇒ (1, 5)
x = 5 : y = (2 × 5) + 3 = 10 + 3 = 13 ⇒ (5, 13)
Solutions are (1, 5) and (5, 13)